(untitled) (Tábano, 2025)
For Deleuze, ethics is an experimental knowledge: it is about composing relations, testing whether a new connection increases the body’s potency or its depotency. This article pursues a central objective: to show the elements necessary for the construction of an immanent and relational ethics that is not based on the model of moral judgment, but rather as an experimental praxis based on Deleuze’s interpretation of Spinoza’s ethics and Nietzsche’s philosophy.